Flood Damage Map and Economic Loss Assessment by Google Earth Engine in Case of Rice in 2021 of Ayutthaya Province, Thailand - Keola, Souliya; Suttinon, Pongsak (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
The central region of Thailand is the most economical flow. Nevertheless, Ayutthaya Province has suffered from flood events annually. Near real-time flood mapping has potential for flood damage reduction measurement. This flood map is generated, using Google Earth Engine (GEE) Cloud-based by gathering the global surface imageries from Sentinel-1 synthetic aperture radar (SAR) by analyzing the pre- and post-flooded images, with land use dataset from MODIS and digital elevation model (DEM) from WWF’s HydroSHEDS to determine the affected areas and to evaluate direct-damage of rice in term of economic loss. This research concentrates on the damage matters to rice only. In 2021, a storm named Dian-Mu was the worst that impacted the central region of Thailand. As a result, Ayutthaya flooded over 475,512.36 RAI, and we estimated rice would be lost 1.877 billion THB.